The Disk Substructures at High Angular Resolution Project (DSHARP): III. Spiral structures in the millimeter continuum of the Elias 27, IM Lup, and WaOph 6 disks - Huang, Jane; Dullemond, Cornelis (Arxiv, 2018)
We present an analysis of ALMA 1.25 millimeter continuum observations of spiral structures in three protoplanetary disks from the Disk Substructures at High Angular Resolution Project. The disks around Elias 27, IM Lup, and WaOph 6 were observed at a resolution of $\sim40-60$ mas ($\sim6-7$ au). All three disks feature $m=2$ spiral patterns in conjunction with annular substructures. Gas kinematics established by $^{12}$CO $J=2-1$ observations indicate that the continuum spiral arms are trailing. The arm-interarm intensity contrasts are modest, typically less than 3. The Elias 27 spiral pattern extends throughout much of the disk, and the arms intersect the gap at $R\sim69$ au. The spiral pattern in the IM Lup disk is particularly complex-it extends about halfway radially through the disk, exhibiting pitch angle variations with radius and interarm features that may be part of ring substructures or spiral arm branches. Spiral arms also extend most of the way through the WaOph 6 disk, but the source overall is much more compact than the other two disks. We discuss possible origins for the spiral structures, including gravitational instability and density waves induced by a stellar or planetary companion. Unlike the millimeter continuum counterparts of many of the disks with spiral arms detected in scattered light, these three sources do not feature high-contrast crescent-like asymmetries or large ($R>20$ au) emission cavities. This difference may point to multiple spiral formation mechanisms operating in disks.